Male and Female Students’ Language in Performing Request - Sri Wahyuni Hasibuan; Lince Sihombing (LINGUISTIK TERAPAN, 2016)
The objective of this study were 1) to find out the kinds of request used by male and female students in doing interaction at informal context, 2) to elaborate the way request linguistically performed by male and female students in doing interaction at informal context, and 3) to provide the reasons why male and female students perform request in the way they are. It was applied by using descriptive qualitative research.  It was conducted at Dharmawangsa Senior High School in Medan involving 3 male and 3 female students. The data were collected through observing, recording and interviewing them. The data were 44 male students’ utterances and 42 female students’ utterances taken in three areas of school: canteen, in front of the class, and parking lot. The findings showed that 1) syntactical realization and lexical realization were found in students’ utterances with four kinds of syntactical realization: imperative, interrogative, declarative, and modal auxiliary; 2) the way of requests linguistically performed by male students was the direct way. Similarly, the way of requests linguistically performed by female students was the direct way. 3) There were two reasons why male and female students perform request namely interlocutors and age. Keywords: Male and Female Students, Gender, Request